Remote Control Switching System Based on Wireless Technology - Sekartaji, Luh Kadek Pracanthi Dyah; Pramaita, Nyoman; Gunantara, Nyoman (Journal of Electrical, Electronics and Informatics, 2019)
Remote control switching system is used to control the switching of the electrical and electronic appliances from a distance. This remote serves to facilitate the use of the switching of electrical, and electronic appliances for people with disabilities, and the elderly. This paper develops a remote control system using radio frequency technology utilizing the principle of wireless system. The remote control system is constructed by RF433 module as the transmitter, and receiver, IC HT12E module as the encoder, and IC HT12D module as the decoder. To achieve the aim of this research: a transmitter system is designed to transmit a signal when the keypad is pressed; a receiver system is designed to receive the signal from the transmitter system, then the system will turn on and turn off the loads. Based on experimental results, this design system is capable to turn on and turn off the loads with a transmission distance up to 18 meters, without obstruction, and 15 meters with obstruction.